Virtual Microscopy Beyond the Pyramids, Applications of WSI in Cairo University for E-Education & Telepathology - Essam Ayad; Yukako Yagi (Analytical Cellular Pathology)
Background: Telepathology, the practice of pathology at a long distance, has advanced continuously since 1986. The progress of telepathology passed through four stages: Static, Dynamic, Hybrid & Whole Slide Imaging.